STRATEGI BADAN PENGAWAS PEMILIHAN UMUM DALAM MENCEGAH PELANGGARAN PEMILU TAHUN 2024 (STUDI PADA BAWASLU KOTA MATARAM) - Hidayat, Moh. Dimaz Prasetia; Musyawwir, Abal Wahid; Azhari, Nabila Fatya; Hidayat, Rullian; Haerunnisa, Siti; Kurniawansyah, Edy (Universitas Sulawesi Tenggara, 2024)
This study aims to analyze the strategies implemented by Bawaslu Kota Mataram in preventing election violations in 2024 and to identify the supporting and inhibiting factors in oversight execution. This research uses a qualitative descriptive approach, collecting data through interviews, observations, and document analysis. The results show that the implemented strategy comprises three main stages: preparation, socialization, and evaluation. In the preparation stage, Bawaslu conducted training for election supervisors, developed SOPs, and coordinated with stakeholders. Socialization was carried out through public discussions, social media, and collaboration with educational institutions. The evaluation stage included direct supervision, the use of online reporting technology, and regular evaluation meetings. Supporting factors include community leader support and technology utilization, while challenges involve limited budgets, digital literacy issues, and geographical constraints. A comprehensive and inclusive strategy is required to enhance the effectiveness of election oversight in Kota Mataram.